Determination of fumonisins B1 and B2 in herbal tea and medicinal plants in Turkey by high-performance liquid chromatography - (:unkn) unknown (My University, 2004)
The purpose of this study was to measure the potential levels of fumonisin B1 (FB1) and fumonisin B2 (FB2) contamination in several herbal teas and medicinal plants that are consumed regularly in Turkey. FB1 and FB2 were detected using high-performance liquid chromatography with fluorescence detection after derivatization with o-phthaldialdehyde. A total of 115 commercially available herbal tea and medicinal plant samples were analyzed. The recoveries in black tea were 86.9+/-8.42% for FB1 and 102+/-6.80% for FB2 spiked with 1 microg/g of each analyte. Similarly, the mean recovery results in lime (linden) for FB1 and FB2 were 85.2+/-9.76% and 78.6+/-5.67%, respectively. The minimum detectable amounts for the o-phthaldialdehyde derivatives of FB1 and FB2 were 0.025 microg/g (1 ng injected) and 0.125 microg/g (5 ng), respectively. FB1 was detected in two samples (0.160 and 1.487 microg/g), and FB2 was detected in none of the samples.
Keywords: Turkey; Sensitivity and Specificity; Plants, Medicinal; Tea; Food Contamination; Chromatography, High Pressure Liquid; Fluorescence; Fumonisins; Fusarium